Molecular detection of six RNA viruses in tuber sprouts of potato (Solanum phureja) in Antioquia, Colombia (Bioagro, 2020)
Due to its high internal demand and export potential, potato (Solanum phureja) has become one of the most promising crops for the high Andean region of South America. In Antioquia, Colombia, the S. phureja crop is affected by a complex of viruses that have a very significant effect on yield and tuber-seed quality. In this work, we have investigated the incidence of six RNA viruses (PLRV, PVS, PVV, PVX, PVY and PYVV) in sprouts from the tuber-seeds used by farmers to start their new crop cycles. Detection of these viruses by real-time RT-PCR (RT-qPCR) revealed 100 % incidence of PVS and PYVV and intermediate levels for PLRV (46.66 %), PVY (46.66 %), PVX (40.0 %) and PVV (40.0 %). The circulation of these viruses in eastern Antioquia was confirmed by Next-generation sequencing (NGS) of bulked leaf samples. Complete genome sequences were obtained for all viruses under study with the exception of PYVV, of which only partial segments could be obtained. In addition, NGS also revealed the presence of bell pepper alphaendornavirus (BPEV), which is the first report for this virus infecting potato in Colombia. Phylogenetic analyses on sequences derived from NGS and RT-qPCR demonstrated that PLRV, PVS, PVV, PVX, PVY and PYVV are all related to Colombian isolates sharing nucleotide sequence identities above 95 %. These results reveal an urgent need to establish a tuber-seed certification program for S. phureja in Colombia.
Keywords: Carlavirus; crinivirus; polerovirus; potexvirus; potyvirus; real-time RT-PCR; next generation sequencing